Zebrafish as a Model to Unveil the Pro-Osteogenic Effects of Boron-Vitamin D3 Synergism - Sojan, Jerry Maria; Gundappa, Manu Kumar; Carletti, Alessio; Gaspar, Vasco; Gavaia, Paulo; Maradonna, Francesca; Carnevali, Oliana (Frontiers in Nutrition, 2022)
The micronutrient boron (B) plays a key role during the ossification process as suggested by various in vitro and in vivo studies. To deepen our understanding of the molecular mechanism involved in the osteogenicity of boron or its interaction with vitamin D3 (VD), wild-type AB zebrafish were used for morphometric analysis and transcriptomic analysis in addition to taking advantage of the availability of specific zebrafish osteoblast reporter lines. Firstly, osteoactive concentrations of B, VD and their combinations were established by morphometric analysis of the opercular bone in alizarin red-stained zebrafish larvae exposed to two selected concentrations of B, 10 and 100 ng/ml, one concentration of VD, 10 pg/ml and their respective combinations. Bone formation, as measured by opercular bone growth, was significantly increased in the two combination treatments than treatment with VD alone. Subsequently, a transcriptomic approach was adopted to unveil the molecular key regulators involved in the synergy. Clustering of differentially expressed genes (DEGs) revealed distinct expression patterns towards bone and skeletal functions in the group co-treated with boron and VD. Downstream analysis confirmed MAPK as the most regulated pathway by the synergy groups in addition to TGF-β signaling, focal adhesion and calcium signaling. The best performing synergistic treatment, B at 10 ng/ml and VD at 10 pg/ml, was applied to two zebrafish transgenic lines, Tg(Ola.sp7:mCherry) and Tg(bglap:EGFP), at multiple time points to further explore the results of the transcriptomic analysis. Regarding osteoblast differentiation, the synergistic treatment with B and VD induced an enrichment of intermediate (sp7+) osteoblast at 6- and 9-days post fertilization (dpf) and of mature (bglap+) osteoblasts at 15 dpf. The results obtained here validate the role of B in VD-dependent control over bone mineralization and may help widening the spectrum of therapeutic approaches to alleviate pathological conditions caused by nutritional VD deficiency by using low concentrations of B as nutritional additive.